Pengaruh Jumlah Penduduk, Upah Minimum dan Pertumbuhan Ekonomi Terhadap Pengangguran di Jawa Barat: (The Effect of Population, Minimum Wage and Economic Growth on Unemployment in West Java) - Ghozali, Achmad Ainul; Aji, Tony Seno (Jurnal Ekonomika : INDEPENDEN, 2024)
Abstract Unemployment is a problem that often occurs in various countries. Both in developing countries and also in developed countries, Indonesia is no exception. This unemployment occurs because there are few job opportunities compared to the increasing workforce growth. Population numbers, minimum wages and economic growth are several factors in the unemployment problem. This research aims to determine the effect of population, minimum wage and economic growth on unemployment in West Java. This research uses secondary data from the Central Statistics Agency. The analysis technique used is panel data regression using the Fixed Effect model with the results that population has a negative effect on unemployment, the minimum wage has a positive effect on unemployment, and economic growth has a negative effect on unemployment.